Estimating daily net radiation flux (Rn) using remote sensing technique - Nurliyana, Md Asar (2009)
Daily net radiation (R24n) is key variable in hydrological studies. This study highlight Remote Sensing (Rs) technique for derivation of R24n. Satellite image was used in order to determine spatially distributed information on daily net radiation using land surface temperature, albedo and short wave radiation. Reasonable estimates of R24n were obtained for spatially distributed Land use and Land cover (LULC).